Application of LCoS to dynamical focusing in an optical system - Goldin, M. (2008)
Imaging of samples by different microscopy techniques has produced a relevant impact in the development of new diagnosis techniques in biology, medicine and material science. In many biological, applications, where the sample changes or moves during the observation, a moving spot to track an identified sample is required. We introduce here an optical system that can perform, this tracking without mechanical components. The system, is based on the use of a high resolution liquid crystal on silicon (LCoS) device working as a mostly phase wave front modulator. The additional advantage of this system is performing the motion of the spot at video rate. In general, these devices produce coupled phase and amplitude modulation responses as a function of the applied voltage. This coupling effect deteriorates the response of those ideal optical elements designed as phase only or amplitude only functions. By means of an elliptical polarization light we can reduce the amplitude modulation and improve the phase modulation. We have experimentally found a configuration where the amplitude is almost constant while the phase reaches a high modulation. For this configuration we show how the spot can be moved through, focus plane by means of linear phases, or displaced out of this plane by using a quadratic phase. © 2008 American Institute of Physics.